PERANCANGAN IDENTITAS VISUAL OBJEK WISATA CURUG LUHUR SUKABUMI SEBAGAI STRATEGI PENGUATAN CITRA MELALUI PENDEKATAN DESIGN THINKING: DESIGNING THE VISUAL IDENTITY OF CURUG LUHUR TOURISM DESTINATION IN SUKABUMI AS A STRATEGY FOR IMAGE ENHANCEMENT THROUGH A DESIGN THINKING APPROACH - Harris Effendi; Dida Nurhaida; Fajar Rezandi; Erin Valencia; Ekananda Haryadi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Designing The Visual Identity Of Curug Luhur Tourism Destination In Sukabumi As A Strategy For Image Enhancement Through A Design Thinking Approach. Tourism destinations require strong and consistent visual identities to communicate their unique character and enhance recognition among visitors. Curug Luhur, a natural attraction in Sukabumi, currently lacks a coherent logo, tagline, and visual guideline, resulting in weak brand visibility. This research aims to strengthen the image of Curug Luhur tourism destination through the design of a visual identity using the Design Thinking approach. The study was conducted collaboratively with local residents and village authorities, following the stages of empathize, define, ideate, prototype, and test. The final design, featuring waterfall and foliage elements in turquoise tones, effectively reflects the natural charm of Curug Luhur. A perception test involving 30 respondents yielded over 85% positive responses in terms of aesthetics, readability, and meaning relevance. The resulting visual identity guideline serves as a strategic tool to ensure communication consistency and reinforce destination branding. Beyond visual outputs, this research also contributed to enhancing community capacity in creative visual promotion and supporting the growth of local creative economy initiatives related to tourism.